Frictional Characteristics of Steel Materials Sliding against Mild Steel - Nuruzzaman, D. M.; Chowdhury, M. A.; Rahaman, Mohammad Lutfar (Trans Tech Publications, Switzerland, 2014)
In this study, friction coefficients of different steel materials are investigated and compared. Experiments are carried out when different types of steel discs such as stainless steel 201 (SS 201), stainless steel 301 (SS 301) and mild steel slide against mild steel pin. Experiments are conducted at normal load 5, 7.5 and 10 N, sliding velocity 0.5, 0.75 and 1 m/s and relative humidity 70%. The effects of duration of rubbing on the friction coefficient of different steel materials are investigated. Results show that during friction process, test disc takes less time to stabilize with the increased normal load or sliding velocity. It is found that friction coefficient decreases with the increase in normal load while it increases with the increase in sliding velocity for all the tested materials. As a comparison, it is found that at identical operating conditions, friction coefficients are different for different steel materials depending on normal load or sliding velocity.